Adherence to the Cooperative Principle Among Characters in the Film Miracle in Cell No. 7 - Diana Khoeriyah Nuraeni; Uki Hares Yulianti; Nur Indah Sholikhati (Journal of linguistics, culture and communication, 2025)
This study aims to examine the form of compliance with Grice's cooperative principles in the film Miracle in Cell No. 7. Cooperative principles are an important aspect in creating effective and harmonious communication between speakers and their interlocutors. Films were chosen as the object of study because they present communicative interactions that reflect human values amid social limitations. This study uses a qualitative approach with a descriptive method. Data were collected from the characters' utterances using listening techniques, followed by the non-participatory observation technique (Simak Bebas Libat Cakap) and note-taking, as well as element sorting techniques. The findings show that all four maxims of cooperation were observed: 22 instances of the maxim of quantity, 13 instances of the maxim of relevance, 4 instances of the maxim of manner, and 2 instances of the maxim of quality, totaling 41 instances. The dominance of quantity is influenced by the police and legal context, which demands concise information and asymmetrical power relations. At the same time, the low compliance with the quality and manner maxims is related to conflict and emotional tension in the storyline. Overall, this study shows that the characters' communication patterns are directed at building effective and cooperative interactions, while reflecting the messages of humanity, empathy, and solidarity that are at the heart of the story. This study focuses on maxim compliance as a form of communicative cooperation that is in line with the film's theme of humanity.